2019
DOI: 10.1177/0706743719874178
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health among Canadian Postsecondary Students: A Mental Health Crisis?

Abstract: Objective: Recent reports express concerns about a mental health crisis among postsecondary students. These assertions, however, often arise from surveys conducted in postsecondary settings that lack the broader context of a referent group. The objectives of this study were (1) to assess the mental health status of postsecondary students 18 to 25 years old from 2011 to 2017 and (2) to compare the mental health status of postsecondary students to nonstudents. Methods: Prevalence was estimated for a set of menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 17 publications
3
26
1
Order By: Relevance
“…Therefore, the post-secondary environment is not necessarily creating an increase in the prevalence of mental illnesses, though it may be a contributing factor. Notably, recent research has shown that post-secondary students do not appear to have worse mental health than the general population, therefore challenging the notion of there being a “mental health crisis” among the Canadian post-secondary student population [ 35 ]. This is not to say that post-secondary mental health in Canada does not deserve attention, but suggests that mental health care for emerging adults both within and outside of the post-secondary institution must be bolstered.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the post-secondary environment is not necessarily creating an increase in the prevalence of mental illnesses, though it may be a contributing factor. Notably, recent research has shown that post-secondary students do not appear to have worse mental health than the general population, therefore challenging the notion of there being a “mental health crisis” among the Canadian post-secondary student population [ 35 ]. This is not to say that post-secondary mental health in Canada does not deserve attention, but suggests that mental health care for emerging adults both within and outside of the post-secondary institution must be bolstered.…”
Section: Discussionmentioning
confidence: 99%
“…Although post-secondary students do not struggle with mental health issues at a greater rate than non-students in the same age group (Wiens et al, 2020), there is a concerningly high prevalence of mental health issues among post-secondary students. A 2019 survey of post-secondary institutions in Canada found that in a 12-month period, 69% of student respondents had experienced overwhelming anxiety, 64% felt that things were "hopeless", 51% reported feeling overwhelming anger, 52% felt so depressed that they had difficulty functioning, and over 16% reported seriously considering suicide (ACHA-NCHA, 2019).…”
Section: Introductionmentioning
confidence: 93%
“…[15][16][17][18][19][20][21] These results have been often interpreted as a "mental health crisis" and an "epidemic of mental disorders" on campus with calls for more therapy and other mental health speciality services as a response, [22][23][24][25][26][27] despite the fact that the prevalence of mental disorders among young people has been relatively stable over decades. [28][29][30][31][32] These data reporting high rates of increases in perceived mental disorders in the face of stable prevalence suggest that some young people may not be able to distinguish normal existential stresses from a mental disorder due to a lack of mental health literacy. [33][34][35] Similarly, this suggests that providing young people who are transitioning to postsecondary schooling with information that could enhance their mental health literacy while concurrently addressing the common and normal stress-inducing situations that they are likely to experience may be a useful mental health intervention.…”
Section: Introductionmentioning
confidence: 99%